2018
DOI: 10.1002/ece3.4001
|View full text |Cite
|
Sign up to set email alerts
|

Phenological responses to nitrogen and water addition are linked to plant growth patterns in a desert herbaceous community

Abstract: Increases in nitrogen (N) deposition and variation in precipitation have been occurring in temperate deserts; however, little information is available regarding plant phenological responses to environmental cues and their relationships with plant growth pattern in desert ecosystems. In this study, plant phenology and growth of six annuals in response to N and water addition were monitored throughout two consecutive growing seasons in 2011 and 2012 in a temperate desert in northwestern China. The effects of N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 69 publications
5
25
0
Order By: Relevance
“…Many studies have shown that water plays an important role in driving plant phenology, such as budburst ( Hayden et al., 2010 ), green-up ( Zhang et al, 2005 ; Liu et al., 2013 ), flowering ( Crimmins et al., 2010 ; Lesica and Kittelson, 2010 ; Crimmins et al., 2011 ; Crimmins et al., 2013 ; Kigel et al., 2013 ; Sakkir et al., 2014 ; Huang et al., 2018 ), and fruiting ( Lotfi and Mohamed, 2006 ; Galindo et al., 2014 ), in water-limited ecosystems. However, most of these studies are focused on natural conditions, while the relationship between water increase and phenological events based on water addition experiments has not been explored, nor has the effects of water addition on branch phenology of desert plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have shown that water plays an important role in driving plant phenology, such as budburst ( Hayden et al., 2010 ), green-up ( Zhang et al, 2005 ; Liu et al., 2013 ), flowering ( Crimmins et al., 2010 ; Lesica and Kittelson, 2010 ; Crimmins et al., 2011 ; Crimmins et al., 2013 ; Kigel et al., 2013 ; Sakkir et al., 2014 ; Huang et al., 2018 ), and fruiting ( Lotfi and Mohamed, 2006 ; Galindo et al., 2014 ), in water-limited ecosystems. However, most of these studies are focused on natural conditions, while the relationship between water increase and phenological events based on water addition experiments has not been explored, nor has the effects of water addition on branch phenology of desert plants.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation increases likely impose substantial impacts on plant phenology in these deserts in response to climate change. Few studies examined the effects of water addition on reproductive phenology of six annuals on the southern fringe of the Gurbantunggut Desert in northwestern China and the results were only based on a short-time manipulative experiment (Huang et al, 2018). The results showed that water addition consistently advanced both the flowering and fruiting time of four spring ephemerals; however, their effects on two spring-summer annuals were inconsistent, where advances were found in one species, while delays were found in another (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also affects species distribution, community characteristics (Xu et al, 2007;Li et al, 2010), and plant zonation (Cooper et al, 2006;Rzepecki et al, 2011) by driving water availability (Liu et al, 2017). Precipitation patterns influence the aboveground net primary production of sand-fixing vegetation (Li and Zhao, 2017), community structure (Cheng et al, 2006), annual plant phenology (Huang et al, 2018), photosynthesis (Liu et al, 2012), and carbon cycle (Thomey et al, 2011). Dune mobility affects the settlement and expansion of desert plants (Hernández-Cordero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%